A Comparative Study on the Curriculum Objectives of Cadets and the School of Undergraduate Police Inspectors (SIPSS) at the Police Academy - Aulia, Firdatul Izza; Nirmala, Nirmala (South Sulawesi Education Development (SSED), 2025)
This study aims to analyze and compare the formulation of curriculum objectives in the Cadets education program and the Undergraduate Police Inspector School (SIPSS) at the Police Academy. Using the qualitative case study approach, data were collected through interviews, observations, and documentation of curriculum documents and related materials. The results of the study indicate that the formulation of the cadet curriculum's objectives focuses on developing police officers with field leadership skills, strong character, and mastery of tactical and operational aspects. Meanwhile, the SIPSS curriculum focuses on strengthening professional competencies based on academic backgrounds to support the specific needs of the National Police organization. These differences reflect the National Police's differential strategy in preparing officers who are responsive to increasingly complex institutional and social challenges.